The Development of Higher Education System in Turkmenistan: Current Social, Economic, and Political Changes - A. M. Pogorelskaya (Moscow Polytechnic University, 2021)
The article analyzes the transformation of higher education system in Turkmenistan. The aim of the research is to evaluate the prospects of Russian higher education export to Turkmenistan taking into account the  peculiarities of Turkmen higher education system and the main trends affecting it. The role of the state and the influence of global trends on  Turkmen higher education system in 1991-2020 are estimated based on the coordination model and the concept of higher education  internationalization. Since Turkmenistan as well as many other countries  aims at increasing its universities' popularity in the world, the article also considers the degree of internal and external higher education internationalization. Taking into consideration the peculiarities of the national economy of Turkmenistan, the political system, and the power balance in Central Asia, the author seeks to forecast the development of Turkmen higher education system. The article concludes that there is a significant potential for increasing the export of Russian higher education services to Turkmenistan.  However, Russian universities need to explore the peculiarities of the country  and elaborate suitable methods of work with Turkmen school-leavers.